The Biology of the African Bonytongue Heterotis niloticus (Cuvier, 1829) from the Lower Niger River at Agenebode in Edo State, Nigeria - M. O. Agbugui; H. O. Egbo; F. E. Abhulimen (International Journal of Zoology)
Background. The African bonytongue, Heterotis niloticus, is readily accommodated in the fresh water of the Niger River. It is available all year round with a large population of juveniles and adults due to its fast growth and versatile feeding habits. This commercial fish is a highly preferred source of food because of its high protein content and hardy flesh, thus forming a very important component in the diet of many Nigerians. It is highly valued because of its socioeconomic importance and benefits. Hence, this research is designed with the aim of studying the biology of the African bonytongue, Heterotis niloticus, and providing viable information about its importance in fish culture in order to make an available added variety of culturable and affordable fish species in Nigeria. Results. The oesophagus is a muscular organ that is short and distensible. The oesophagus leads to the gizzard-like stomach, a reddish bilobed organ that is muscular and tough. H. niloticus is an omnivorous macrophage detritor, consuming a wide variety of bottom-dwelling food items. The histology of the gastrointestinal tract reveals four conspicuous layers from the inside to the outside: mucosa, submucosa, inner circular layer and outer longitudinal layer of muscularis, and serosa. The presence of numerous mucus glands and longitudinal folds with a prominent columnar epithelium provides durable length or an extension of the gut mucus to aid lubrication and easy passage of food materials, protecting the mucosal epithelium from mechanical or chemical injuries arising from interactions with digestive tract contents or enzymes. In addition, the presence of absorptive cells helps in the absorption of valuable nutritive substances. Conclusions. The anatomy of the mouth and gut and the aforementioned histology are modified to accommodate the feeding habits. H. niloticus has a single ovary that rests on the right side of the fish; it is reproductively active as the flood plains rise and peaks at the peak of the rains, being a moderately fecund fish. The high fecundity is complemented with peaks of GSI observed during the months of September, October, and November, which reveals spawning periods. Hence, the aforementioned attributes of H. niloticus make the fish a viable fish species for culture.